Estimation of percolating water dynamics through the vadose zone of the Postojna cave on the basis of isotope composition - Kogovšek, Janja; Urbanc, Janko (Geologija, 2007)
Within the scope of monitoring water percolation through the 100-m thick vadose zone in the area of Postojnska jama continuous measurements of precipitation were carried out on the surface, and continuous measurements of water flow and physical and chemical parameters of selected water trickles were performed under the surface. Occasional samples of percolating waters were taken for the analysis of water oxygen isotope composition. An exponential model of groundwater flow was elaborated, by means of which the retention time of water in individual trickles was estimated. Modelled retention times of groundwater range from 2.5 months to over one year.